Non-invasive assessment for alpha-1 antitrypsin deficiency-associated liver disease: new insights on steatosis and fibrosis in Pi*ZZ carriers - Roohani, Siyer; Tacke, Frank (Translational Gastroenterology and Hepatology, 2019)
One in every 5,000 individuals is expected to be affected by the hereditary alpha-1 antitrypsin deficiency (AATD) predisposing to liver cirrhosis, hepatocellular carcinoma and chronic obstructive pulmonary disease (COPD).